An exploration of how masculinity/ies is/are perceived to influence the help-seeking behaviours of men who have survived rape : the rape counsellors’ perspectives - Martin, Jarrred H. (University of Pretoria, 2021)
Mini Dissertation (MA (Research Psychology))--University of Pretoria, 2021.